2021
DOI: 10.1101/2021.10.04.21264434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute COVID-19 gene-expression profiles show multiple etiologies of long-term sequelae

Abstract: Two years into the SARS-CoV-2 pandemic, the post-acute sequelae of infection are compounding the global health crisis. Often debilitating, these sequelae are clinically heterogeneous and of unknown molecular etiology. Here, a transcriptome-wide investigation of this new condition was performed in a large cohort of acutely infected patients followed clinically into the post-acute period. Gene expression signatures of post-acute sequelae were already present in whole blood during the acute phase of infection, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Notably, these patients did not statistically differ in various metrics of clinical severity in hospital [ e.g. , highest recorded SOFA score and World Health Organization COVID-19 Clinical Progression Score ( 45 )], cell proportions, lab values, treatments received, rates of ICU admission, and hospitalization duration compared to patients without post-COVID symptoms (termed “asymptomatic”) ( Table 1 ), which was consistent with the literature indicating that the presence of these post-COVID symptoms is not associated with disease severity ( 46 ), since many mild and even non-hospitalized patients can also develop persistent symptoms ( 7 , 8 ). In addition, common confounders including age and sex, as well as the time between discharge date and follow-up date, were not statistically different between these two groups.…”
Section: Resultssupporting
confidence: 84%
“…Notably, these patients did not statistically differ in various metrics of clinical severity in hospital [ e.g. , highest recorded SOFA score and World Health Organization COVID-19 Clinical Progression Score ( 45 )], cell proportions, lab values, treatments received, rates of ICU admission, and hospitalization duration compared to patients without post-COVID symptoms (termed “asymptomatic”) ( Table 1 ), which was consistent with the literature indicating that the presence of these post-COVID symptoms is not associated with disease severity ( 46 ), since many mild and even non-hospitalized patients can also develop persistent symptoms ( 7 , 8 ). In addition, common confounders including age and sex, as well as the time between discharge date and follow-up date, were not statistically different between these two groups.…”
Section: Resultssupporting
confidence: 84%
“…The prognosis in the acute phase of the disease has been mainly linked to the severity of the respiratory involvement (including the development of acute respiratory distress syndrome (ARDS), the need for admission to intensive care units (ICUs), and mechanical ventilation), the length of hospital stay (LOS), the levels of some inflammatory markers, and previous comorbidities [ 4 6 ]. Moreover, studies focusing on transcriptomics have suggested that a small set of regulatory genes might act as strong predictors of patient outcomes [ 7 , 8 ]. Two years into the pandemic, the long-term sequelae of COVID-19 are exacerbating the global health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic and genomic research could shed light on the reasons why certain individuals present post-COVID-19 sequelae, allowing us to design drugs to prevent it. Thompson et al [ 7 ] have been able to directly link these sequelae to the host response to the virus.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most biological assessments of PASC have focused on the post-acute phase of infection (4,(6)(7)(8)(9)(19)(20)(21)(22)(23)(24)(25). Only a few studies have assessed the relationship between biomarkers in the acute phase of SARS-CoV-2 infection and the later development of PASC (12,13,26). Such efforts have identified the presence of SARS-CoV-2 RNA in blood at the time of diagnosis (26) and prolonged duration of viral shedding from the upper respiratory tract (12) as correlates of PASC.…”
Section: Discussionmentioning
confidence: 99%